Acceptability of COVID-19 vaccine in the working-age population in Shanghai city: a cross-sectional study. Issue 11 (2nd November 2021) - Wu, Linlin; Huang, Zhuoying; Guo, Xiang; Liu, Jiechen; Sun, Xiaodong
ABSTRACT: Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is still an enormous threat to global health and the economy. Although China has adopted effective measures to control the outbreak, there is still a risk of local transmission from imported cases. Meanwhile, considering the high mortality rate and rapid spread of the disease, a safe and effective vaccine is urgently needed to control the pandemic. With COVID-19 vaccines becoming available to the population, it has become important to know about their acceptance in the population. This is important to enable high vaccination coverage rates and reflects the demand within the general population. An cross–sectional survey was conducted during October 2020 in Shanghai using a well-designed questionnaire, which aimed to evaluate the acceptability of COVID-19 vaccines and to identify the factors affecting its acceptability among working-age adults in Shanghai, China. We found that the acceptability of COVID-19 vaccines was high in work-age adults in Shanghai, China. The factors affecting the acceptability of vaccination identified in this study can provide guides to increase COVID-19 vaccine acceptability in future.